NURSING MANAGEMENT THE RISK OF NUTRITION IMBALANCE LESS THAN BODY IN An. S WITH TYPHOID FEVER IN SPACE SEKARJAGAD RSUD BENDAN KOTA PEKALONGAN - Mardi Hartono; Rr Sri Sedjati; Petrus Nugroho Djoko Santoso; Eka Nofianti (Poltekkes Kemenkes Semarang, 2020)
ABSTRACBackground : Typhoid fever is an acute infectious disease caused by salmonella typhi bacteria and attacks the digestive system. Cases of typhoid fever in Indonesia are estimated to reach 800 sufferers per 100.000 Indonesian population each year with the highest percentage occurring in children aged 5-14 years. Typhoid fever sufferers tend not to have an appetite so that they experience nutritional imbalances that are less than the body’s needs or risk an imbalance of nutrients less than the body’s need.Objective : This study aims to obtain an overview of nursing management risk of nutritional imbalance less than body’s needs in children with typhoid fever in the Sekarjagad room at Bendan Distric Hospital.Method : The research method used in the preparation of scientific papers is descriptive research design, namely the research method used to solve or answer problems that are being faced in the current situation. to describe nursing care from assessment to nursing evaluation with the subject typhoid fever pediatric patients who are at risk of experiencing nutritional imbalances less than the body’s needs.Resuls : The result of research on patient showed that the management of the risk of nutritional imbalance is less than body’s needs with motivation given about the importance of nutrition for healing can increase appetite, so the problem of the risk of nutritional imbalance is less than the body’s needs partially resolved.Keyword : The risk of nutritional imbalance is less than the body’s needs, typhoid fever